Identifkasi Bakteri dan Fungi Udara pada Pusat Perbelanjaan di Pangkal Pinang - Helmi, Henny; Vebriani, Helly; Juliani, Intan; Karina, Karina; Junita, Junita (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2023)
Shopping center is one of the densest areas of human activity, so that the gathering of humans can cause transmission of microorganisms that cause air borne disease. This research was conducted to find out the various types of air pollutant bacteria and fungi on the 2nd Floor of One of the Shopping Center Areas in Pangkal Pinang City. This research was conducted experimentally using Nutrien Agar and Potato Dextrose Agar media for enumeration of bacteria and fungi. Identification of bacteria and fungi was carried out macroscopically, microscopically and biochemically. The results of this study showed that there were 9 bacterial isolates and 4 fungal isolates. The genus of bacteria found is Bacillus sp. Staphylococcus sp. and Nitrobacter sp. As for the genus of fungi found, among others, namely Aspergillus sp. The total bacteria and fungi present in the air in the shopping center have not exceeded the quality standards that have been set, so that it can be said that the air in one of the Pangkal Pinang City Shopping Centers is still healthy